MANAJEMEN APARATUR SIPIL NEGARA DALAM MEWUJUDKAN PROFESIONALISME DAN DAYA SAING APARATUR SIPIL NEGARA - Ellyza Octaleny (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Arrangement of organization and staffing need to be done considering the number of employees and the number of organizations can lead to ineffective administration of government both central and regional. The number of organizational units should indicate a balance with the number of employees. To balance the number of organizational units with the number of employees required human resources management. Human resource management in a government organization is often called civil service management. Current conditions and problems are (1) Employment management has not oriented to human resource management, (2) Distribution of civil servants is less harmonious with the distribution of tasks and functions, (3) Employment system not merit-oriented, (4) Some remuneration has not been linked With duties and responsibilities, (5) The accountability system is still weak. To overcome this, the government will enact Law No. 5 of 2014 on State Civil Apparatus. As the National Strategic Policy of the State Apparatus Empowerment (Jakstrapan) in 2005-2009, the development of human resources of the apparatus is focused on improving the quality of public services and accelerating the eradication of KKN and improving the performance of apparatus through the application of payroll system based on merit and remuneration, accountability and discipline enforcement consistently, institutional vision-mission, and effective management. The strategy undertaken to implement the development of apparatus resources is by applying the principles of good governance at all levels, lines, and government activities. Keywords : apparatus, civil, professional